Triad of impairment in older people with diabetes-reciprocal relations and clinical implications. (March 2020) - Abdelhafiz, A.H.; Davies, P.C.; Sinclair, A.J.
Highlights: Components of the TOI commonly coexist and show a reciprocal relationship. Diabetes increases the risk of TOI and shows a reciprocal relationship with its components. Frailty is better viewed as a complex phenotype of the TOI rather than the physical aspect alone. Older people with diabetes should be assessed periodically for the presence of the TOI. There is a need for novel hypoglycaemic medications that have a positive effect on the TOI. Abstract: Frailty is emerging as a new category complication of diabetes in older people. Clinically, frailty is still not well defined and mostly viewed as a decline in solely the physical domain. However, frailty is a multidimensional syndrome and the newly introduced concept of "triad of impairment" (physical, cognitive and emotional) may be a more representative of the broad nature of frailty. The components of the triad of impairment (TOI) commonly coexist and demonstrate a reciprocal relation. Diabetes in old age appears to increase the risk of the triad of impairment, which may eventually progress to disability. Therefore, older people with diabetes should be regularly assessed for the presence of these three key components. Adequate nutrition and regular resistance exercise training have been shown to have a positive impact on the long-term outcome in this population. However, the role of good glycaemic control and the use of current hypoglycaemic medications in reducing the incidence of this triad are less clear. Future research is needed to develop novel hypoglycaemic medications that not only focus on glycaemic control and cardiovascular safety but also on reducing the risk of the triad of impairment.